PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP INTENSI KELUAR DI UNIT BISNIS PHARMACEUTICAL XYZ INDONESIA - , Yuliana Rama Krisna ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research examined the direct and indirect effect job satisfaction and organization commitment upon turnover intention. Relationship between job satisfaction and organizational commitment was also examined. A quantitative research design was adopted for the research. The final sample consisted of 117 employees who worked in Pharmaceutical Business Unit of XYZ Indonesia through a questionnaire survey measuring job satisfaction, organization commitment and turnover intention. The questionnaire consisted of 46 valid items